Sexual deviance : issues and controversies - Ward, Tony; Laws, D. Richard; Hudson, Stephen M. (Sage Publications, 2003)
In this work, the authors examine why sex offences are committed and covers the controversies surrounding what to do about it. It discusses cutting edge theoretical developments in etiology rehabilitation and practice.